THE INFLUENCE OF SPELLING BEE GAMES TO IMPROVE STUDENTS’VOCABULARY MASTERY IN USING ICD-10 CHAPTER XVIII and XXI AT APIKES IRIS PADANG - Nila Mayasari (Politeknik Negeri Padang, 2019)
Vocabulary has become the key aspect in learning language and it should be introduced through an interesting way. One way to mastery it is through Spelling Bee game. In line with that Lewis and Hill (“1998) stated that student will not achieve success in learning unless they enjoy the process will influence their achievement. This study entitles The Influence Of Spelling Bee Games To Improve Students'Vocabulary Mastery In Using ICD-10 Chapter Chapter XVIII and XXI At Apikes Iris Padang discovers the effectiveness of the use of Spelling Bee in teaching vocabulary. The sample is given Spelling Bee treatment that was adopted from Stone (2010).The data of this study are obtained through a post test.the post- test is given in the form of spelling test. The data from the post test are analyzed statistically using SPSS 20 for windows. The result shows that the lowest score on the post test is 30.00 Meanwhile, the highest score is 95.00. The range of scores was 65.00. Dealing with central tendency, the averange score is 69.9231 and the midpoint fell on 75.0000. Then, the table also presents standart deviation which indicates the average variability of the scores from mean is 1.58482E. From the post –test result it can be seen student really influence by the spelling be game.